O crescimento da Classe C no Brasil e as mudanças na narrativa dos telejornais - Garcia, Maria Teresa (2015)
This thesis analyses the effects of the brazilian social class "C" growth in the television news broadcasts. The work observes how this class loomed in the first decade of this century and reflects the impact this social transformation had in the press. The case study that this thesis proposes is the one of the "Jornal Hoje", from Rede Globo. Editions of the TV news program from 2000 to 2014 were analysed, showing the transformations in the formatting and in the language of its contents. This work also focuses on how communication with the viewer can become more colloquial from the use of the portuguese language oral modality